THE INFLUENCE OF MARKETING MIX ON CONSUMER BUYING INTEREST IN FOREST HONEY OF KAPUAS HULU - Ruchiat, Yayat; Komaladewi, Rita; Kurniatun, Taufani C. (Yayasan Education and Social Center, 2024)
This research was conducted on Kapuas Hulu Forest Honey customers from Jakarta, Pontianak, and Kapuas Hulu to find out and analyze the influence of the marketing mix on their buying interest. The number of samples used was 200. Product, price, location, and promotion were independent variables in this study, and buying interest was a dependent variable. For regression analysis, SPSS 26 is used. The Likert scale was used to measure variables and data analysis was carried out using Multiple Linear Regression Analysis. The results of the analysis show that one product has a positive and significant influence on customer desire to buy Kapuas Hulu Forest Honey; price has a positive and significant influence on customer desire to buy Kapuas Hulu Forest Honey; location has a positive and significant influence on customer desire to buy Kapuas Hulu Forest Honey; and promotion has a positive and significant influence on customer desire to buy Kapuas Hulu Forest Honey